ChemInform Abstract: Aryl Formate as Bifunctional Reagent: Applications in Palladium‐Catalyzed Carbonylative Coupling Reactions Using in situ Generated CO. Issue 36 (9th September 2014) - Li, Haoquan; Neumann, Helfried; Beller, Matthias; Wu, Xiao‐Feng
Abstract The carbonylative reactions rely on the cooperation between phenyl formate and nonaflate and the generation of CO in situ by using aryl formates as the CO source and pseudohalide precursors.